Improvement of Electric Furnace Heating Function for Use in Aluminium Waste Management - Huzaidi, Muhammad Najmi; Paimin, Aini Nazura (Research and Innovation in Technical and Vocational Education and Training, 2023)
A furnace is a widely used tool in metal recycling activities. The use of furnaces is mainly focused on the production of aluminium materials. The heating system for the furnace is an important aspect that will affect the material to be melted. It needs to be at an optimal level to ensure that the melting of each material undergoes a perfect process. The furnace heating system that has been developed before shows some limitations and shortcomings. The problem occurs when the furnace only uses one heating plate. This project was produced to improve the function of the electric furnace used to melt aluminium scrolls resulting from machining activities. This product is developed based on the Engineering Design Process model as a guide for the development of this product which has certain phases of the problem, carrying out research, specification of solutions, prototype design, prototype testing, and improvement. Evaluation is done to test the functionality of the product in solving the heating time problem. As a result of the observations made, the furnace can heat up to 650c between 5 minutes and 48 seconds to 7 minutes and 21 seconds. Based on the analysis, it can be explained that the objectives of the study have been achieved.